PENGARUH PEMBELAJARAN TELENURSING TERHADAP PENGETAHUAN PENCEGAHAN KANKER SERVIKS PADA SISWI SMA NEGRI 1 SERIRIT - Permadani, Ni Putu Putri Cahya; Nurhesti, Putu Oka Yuli; Suindrayasa, I Made (Coping: Community of Publishing in Nursing; Vol 9 No 4 (2021): Agustus 2021, 2021)
Cervical cancer is an abnormal growth of cells in the cervix which is the second largest cause of death in women in the world. Introduction to cervical cancer is very necessary to avoid the effects that can occur. Telenursing can be used to disseminate information regarding cervical cancer prevention. The purpose of this study was to determine the effect of telenursing learning on the prevention of cervical cancer prevention in female students of Senior High Scool 1 Seririt. This type of research was a quasi experiment with one group pre-post test design. This research was conducted from 4 th May to 18 th May 2020 with a total of 45 samples. The research instrument used was a cervical cancer knowledge and cervical cancer prevention questionnaire, the results have been analyzed by Wilcoxon test. The results show that there are 34 people who have less knowledge before learning telenursing. After learning telenursing the level of knowledge of research subjects increased with 40 people with good knowledge. The average score of cervical cancer prevention knowledge respectively for pre-test 8.33 and post-test 16.31. Wilcoxon test results p-value 0,000 (p <0.05) which shows there is an effect of telenursing learning on increasing knowledge of cervical cancer prevention in female students of Senior High Scool 1 Seririt. Health workers can use telenursing as a medium to improve knowledge of cervical cancer in adolescents.